March 2020 PovcalNet Update : What's New - Atamanov, Aziz; Castaneda Aguilar, R. Andres; Fujs, Tony H.M.J.; Dewina, Reno; Diaz-Bonilla, Carolina; Mahler, Daniel Gerszon; Jolliffe, Dean; Lakner, Christoph; Matytsin, Mikhail; Montes, Jose; Moreno Herrera, Laura L.; Mungai, Rose; et al. (World Bank, Washington, DC, 2020)
The March 2020 update to PovcalNet involves several changes to the data underlying the global poverty estimates. Some welfare aggregates have been changed for improved harmonization, and some of the CPI, national accounts, and population input data have been revised. This document explains these changes in detail and the reasoning behind them. In addition to the changes listed here, a large number of new country-years have been added, bringing the total number of surveys to more than 1,900.